Selecting soil hydraulic properties as indicators of soil health: Measurement response to management and site characteristics. Issue 5 (18th July 2022) - Bagnall, Dianna K.; Morgan, Cristine L. S.; Bean, G. Mac; Liptzin, Daniel; Cappellazzi, Shannon B.; Cope, Michael; Greub, Kelsey L. H.; Rieke, Elizabeth L.; Norris, Charlotte E.; Tracy, Paul W.; Aberle, Ezra; Ashworth, Amanda; et al.
Abstract: Farmers, scientists, and other soil health stakeholders require interpretable indicators of soil hydraulic function. Determining which indicators to use has been difficult because of measurement disconformity, spatial and temporal variability, recently established treatments, and the effect of site characteristics on management practice differences. The North American Project to Evaluate Soil Health Measurements includes 124 sites uniformly sampled across a range of soil health management practices in North America in 2019. We compare and recommend indicators of hydraulic function that best characterize soil health. We assessed the relationship of each indicator to a suite of soil inherent properties and climate variables, the response of each indicator to soil health management practices, the effect that soil inherent properties (clay content, sand content, and pH) and climatic variables (10‐yr mean annual precipitation and temperature) had on response to management practices, and the relationship among the responses of the indicators to soil health management practices. Field capacity measured on intact cores (θFC_INTACT ) was the best measure of soil hydraulic function, because it responded to management, represents a direct measure of soil hydraulic function, is proximal to stakeholder values, and its response to management was not significantly influenced by inherent and climatic variables. Other suitable indicators are bulk density, soil organic carbon (SOC), and aggregate stability, which are not direct measures of soil hydraulic function but do respond to management and may be practical in situations in which measuring θFC_INTACT is not. This study informs selection of soil health indicators to measure soil hydraulic function. Core Ideas: Across sites, management changed aggregate stability, C, and bulk density. Management also changed field capacity for intact cores, but not repacked cores. Increased residue, organic nutrient sources, less tillage, each increased field capacity by 4%. Residue retention, organic nutrients and less tillage reduced bulk density by 2–3%. Field capacity for intact cores was the most responsive and direct indicator.